Монгол хэлний ойролцоо зэргэд дэх тэмдэг нэрийн үүрэг: Adjective function in synonymic parallels in Mongolian - Б., Мөнгөнцэцэг (Mongolian Studies, 2023)
Parallel Mongolian language synonyms evident in proverb examples and other materials for cognition and tongue have hardly been researched. Speech side parallel synonyms are based on a reality, human activity and conclusions determined by their characters. 1 he Mongolian languages parallel synonyms ideas are written b adjectives in a result of direct and indirect speeches. Parallel synonyms which evaluate the comparative activities are written by adjectives of quality. Parallel synonyms modal meanings which are determined things by characters are written by adjectives of color, quantity, place and could also be written using mixed grammar. The materials prove that adjectives of place can be understood by their modal meaning.